Evaluating the Treatment Efficacy of Nano-Drug in a Lung Cancer Model Using Advanced Functional Magnetic Resonance Imaging - Huang, Cuiqing; Liang, Jianye; Ma, Mengjie; Cheng, Qingqing; Xu, Xi; Zhang, Dong; Shi, Changzheng; Shang, Ning; Xiao, Zeyu; Luo, Liangping (Frontiers in Oncology, 2020)
Objectives Nano-drug delivery system in an interesting field in precise cancer treatment, but few study has reported the microenvironmental changes after such treatment. This study aimed to detect the hemodynamic and microenvironmental changes in a lung cancer xenograft model after treated with doxorubicin (DOX) encapsulated by a cyclic arginine-glycine-aspartic acid polypeptide modified poly-(lactic-co-glycolic acid) nanosystem (cRGD-PLGA@DOX) using functional magnetic resonance imaging. Materials and methods: Thirty-two tumor-bearing mice were randomly divided into four groups. Group A was treated with 0.9% saline, Group B with 4 mg/kg of doxorubicin, Group C with 2 mg/kg of cRGD-PLGA@DOX, and Group D with 4 mg/kg of cRGD-PLGA@DOX. Intravoxel-incoherent-motion diffusion-weighed imaging (IVIM-DWI) and R2* mapping were performed, and D*, f, D, and R2* values were obtained before and one, two and three weeks after treatment. They were sacrificed for pathological examination after examinations. Results: The reconstructed cRGD-PLGA@DOX was homogeneous, well-dispersed, and spherical in shape, with an average size of 180 nm. Group D demonstrated the smallest tumor volume and highest tumor inhibition rate in three weeks. D value of Group B, C and D manifested an upward trend in three weeks with the highest increase in Group D. D* values shared a similar increased trends with f values in Group A, B and C in three weeks, except Group D. R2* value of Group A gradually increased in three weeks, but the trends were reversed in the treatment groups. D value was significantly negative with Ki-67 expression (r=-0.757, P<0.001) but positive with TUNEL (r=0.621, P<0.001) and PTEN staining (r=0.57, P=0.004). R2* value was closely correlated with HIF-1a (r=0.721, P<0.001). Conclusion: The Nano-drug demonstrated an enhanced anti-tumor effect without the need of increased chemotherapeutic dosage. The tumor microenvironment such as cellular and perfusion changes during treatment can be noninvasively detected by two functional MRI including IVIM-DWI and R2* mapping.